Declining Democracy in East-Central Europe: The Divide in the EU and Emerging Hard Populism - Ágh, Attila (Edward Elgar Publishing Limited, 2019)
The dramatic decline of democracy in East-Central Europe has attracted great interest world-wide. Going beyond the narrow spectrum of the extensive literature on this topic, this book offers a comprehensive analysis of ECE region - Czech Republic, Hungary, Poland, Slovakia and Slovenia - from systemic change in 1989 to 2019 to explain the reasons of the collapse of ECE democratic systems in the 2010s.